2014
DOI: 10.1371/journal.pone.0092962
|View full text |Cite
|
Sign up to set email alerts
|

Dichloroacetate Enhances Adriamycin-Induced Hepatoma Cell Toxicity In Vitro and In Vivo by Increasing Reactive Oxygen Species Levels

Abstract: A unique bioenergetic feature of cancer, aerobic glycolysis is considered an attractive therapeutic target for cancer therapy. Recently, dichloroacetate (DCA), a small-molecule metabolic modulator, was shown to reverse the glycolytic phenotype, induce reactive oxygen species (ROS) generation, and trigger apoptosis in various tumor cells. In this work, the capacity of DCA to enhance Adriamycin (ADM) efficacy in hepatoma cells by modulating glucose metabolism and redox status was evaluated. Two human hepatoma (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 34 publications
2
35
0
Order By: Relevance
“…Furthermore, a case study reported that DCA in combination with omeprazole (a proton pump inhibitor) and/or tamoxifen exhibited synergistic antiproliferative effects on malignant tumors [92]. DCA enhances adriamycin-induced hepatoma cell killing by inducing ROS levels in vitro as well as in vivo [93]. Interestingly, enhancement in sensitization to various anticancer agents in the presence of DCA has been attributed to the modulation of tumor microenvironment, which requires reprogramming of glucose metabolism, perturbations in pH levels, induction of ROS, and modulation of survival pathways [82].…”
Section: Dca Overcomes Resistance and Shows Synergistic Effects Durinmentioning
confidence: 99%
“…Furthermore, a case study reported that DCA in combination with omeprazole (a proton pump inhibitor) and/or tamoxifen exhibited synergistic antiproliferative effects on malignant tumors [92]. DCA enhances adriamycin-induced hepatoma cell killing by inducing ROS levels in vitro as well as in vivo [93]. Interestingly, enhancement in sensitization to various anticancer agents in the presence of DCA has been attributed to the modulation of tumor microenvironment, which requires reprogramming of glucose metabolism, perturbations in pH levels, induction of ROS, and modulation of survival pathways [82].…”
Section: Dca Overcomes Resistance and Shows Synergistic Effects Durinmentioning
confidence: 99%
“…DCA potentiates the cytotoxicity of several chemotherapies and reverses HIF-mediated resistance to bevacizumab in a model of glioblastoma [1116]. Moreover, DCA promoted stable disease in patients with malignant brain tumors in a Phase I trial [22].…”
Section: Introductionmentioning
confidence: 99%
“…found that DCA was able to overcome sorafenib-resistance in a subcutaneous xenograft mouse model with sorafenib-resistant HCC cells [47]. Regarding oral combination therapy, enhanced cytotoxic effects were recently reported for adriamycin with simultaneously administered DCA in hepatoma cells in vitro as well as in subcutaneous mouse xenografts [48].…”
Section: Targeting Cancer Metabolismmentioning
confidence: 99%